Factors Associated with Development among Children in Flood-Prone Areas in Indonesia: - - Tri Peni; Tri Ratnaningsih; Siti Indatul Laili (Alta Dharma Publisher, 2020)
Every natural disaster must cause losses and impacts in the affected area, as well as flooding. Among them are the spread of various germs, loss of property, agriculture, crops, or damaged fields, public facilities, facilities, and infrastructure to be damaged. The purpose of this study was to analyze economic factors, environmental sanitation, nutritional and psychological status of children on children's development in flood-prone areas of Gayaman Village. In this study, the population is all families who have children in flood-prone areas of Gayaman Village. The sampling technique used is purposive sampling. Data were analyzed using the rho spearmen test. The results showed that most children with good psychology with normal development there were 56 respondents (54.9%) with the statistical test results p-value 0.002 the value of the closeness of the relationship was 0.301, meaning that there is a close relationship between child psychology and child development. Respondents were mostly in good environmental sanitation with child normal development to 60 respondents (58.8%). Statistical test results p-value 0.008 the value of the closeness of the relationship is 0.262, meaning that there is a close relationship between environmental sanitation and child development. High socioeconomic with child normal development to 32 respondents (31.4%) with a p-value of 0.079 a closeness value of 0.175, meaning that there is no significant relationship between family economic conditions and child development. The nutritional status of children is mostly good with normal child development of 66 respondents (64.7%) with a p-value of 0.019, a closeness value of 0.232, meaning that there is a close relationship between nutritional status and child development. Good nutritional status in childhood will affect subsequent child development because by providing good nutrition the child is not easily sick and development is optimal.